To solve the equation [tex]\(9 - 4x = 57\)[/tex] step by step, we need to isolate the variable [tex]\(x\)[/tex]. Here's the process:
1. Move the constant term from the left side to the right side:
Subtract 9 from both sides of the equation:
[tex]\[
9 - 4x - 9 = 57 - 9
\][/tex]
Simplifying this, we get:
[tex]\[
-4x = 48
\][/tex]
2. Solve for [tex]\(x\)[/tex] by dividing both sides by -4:
[tex]\[
x = \frac{48}{-4}
\][/tex]
Simplifying this, we obtain:
[tex]\[
x = -12
\][/tex]
Therefore, the value of [tex]\(x\)[/tex] is [tex]\(-12\)[/tex]. Thus, the correct answer is [tex]\( \boxed{-12} \)[/tex].